PEMBERDAYAAN IBU BALITA DALAM KELAS IBU BALITA UNTUK MENINGKATKAN KEMAMPUAN PEMANTAUAN PERTUMBUHAN DAN PERKEMBANGAN BALITA - Yusniarita Yusniarita; Wenny Indah Purnama Eka Sari (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The quality of a child can be assessed from the process of growth and development. The process of growth and development is the result of the interaction of genetic factors and environmental factors. Genetic factors are factors related to genes originating from father and mother, while environmental factors include biological, physical, psychological, and social environments. Children under five are one of the populations most at risk from various health problems. The mother is the closest person to the child who provides care. Mothers must be equipped with sufficient knowledge and skills to stimulate child growth and development. The quality of growth and development of children is determined by the care of the family, especially parents. Mothers are very instrumental in the stimulation and early detection of developmental deviations. Toddler Mother Class is a class where mothers who have children aged between 0 to 5 years jointly discuss, exchange opinions, exchange experiences of fulfilling health services, nutrition and stimulation of growth and development. The empowering mother of children under five in the class of mother of children under five to increase the ability to monitor growth and development of infants aims to improve the ability to monitor growth and development of child.